A I Guerra Mundial na imprensa católica o caso da "Liberdade" - Fontes, Paulo Fernando de Oliveira 1959-; Ferreira, Nuno Estêvão (2022)
The newspaper Liberdade is the starting point for the analysis of the treatment of World War I in the Portuguese Catholic press. To understand the profile of Catholic periodicals during the First Republic, the modes oforganisation of Catholicism during the regime inaugurated in 1910 are observed, including the processes of intervention in the public space and the mobilization the tends of opinion. The newspaper Liberdade followed the 1914-18 conflict according to the central perspectives of its editorial line: defence of Catholics’ freedom of organisation, concerted action by legal means, military chaplaincies and separation between the spheres of action of the Church and the State. The treatment of the First World War was deeply politicised, with issues that were central to Catholicism during the republican regime being put on the agenda: the re-establishment of diplomatic relations between Portugal and the Vatican and religious pacification as a way to internal political stability.
Keywords: Catolicismo; Estado; I Guerra Mundial; Igreja; Imprensa; Portugal